Effect of heated solutions on decay control and residues of imazalil in lemons - Schirra, M.; Cabras, P.; Angioni, A.; Dhallewin, G.; Ruggiu, R.; Minelli, E. V. (Amer Chemical Soc, 1997)
Freshly harvested lemons [(Citrus limon (L.) Burm)] were dipped 3 min in water with and without imazalil (IMZ) at 50, 100, and 200 ppm at 50 degrees C and at 1000 ppm IMZ at 20 degrees C. Following treatments fruit were kept at 9 degrees C and 90%-95% relative humidity (RH) for 13 weeks and an additional week at 21 degrees C and ca. 75% RH, to simulate a marketing period (SMP). No decay control was observed with fruit dipped in water at 50 degrees C. In contrast, IMZ treatments provided 90%-96% control of Penicillium rots during cold storage and SMP. Fungi other than Penicillium spp. were also found in all samples as differences among treatments were negligible. IMZ treatment caused some external damage to the fruit (peel browning), and the percentage of damaged fruit was related to the amount of active ingredient (AI) present in it. Dipping in 200 or 1000 ppm IMZ promoted off-flavor development after 10 weeks of storage, and fruit were judged to be unacceptable for consumption after 13 weeks of cold storage. After 1000 ppm IMZ dipping at 20 degrees C, residue concentration in fruit was 8.20 ppm; this value doubled that found in a previous investigation on lemons treated with comparable IMZ levels. Residue concentrations in fruit after treatment at 50 degrees C was strictly related to the amount of fungicide employed. After 13 weeks Al residues in fruit decreased to average ca. 35% of the initial values. During the 1 week SMP, residue levels decreased by a further ca. 25%. It was concluded that it is possible to achieve significant control of decay in lemons during longterm storage by dipping fruit in 50 ppm IMZ mixtures at 50 degrees C. Such treatment should be advised to remarkably reduce potential pollution in the environment due to packinghouse wastewater disposal.
Keywords: Citrus limon; postharvest; heat treatments; imazalil